2013
DOI: 10.4062/biomolther.2013.067
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of a Butanol Fraction of Rosa hybrida Petals in a Middle Cerebral Artery Occlusion Model

Abstract: The neuroprotective effects of a butanol fraction of white rose petal extract (WRPE-BF) were investigated in a middle cerebral artery occlusion (MCAO) model. Seven week-old male rats were orally administered WRPE-BF for 2 weeks and subjected to MCAO for 2 h, followed by reperfusion. Twenty-four h later, MCAO-induced behavioral dysfunctions were markedly improved in a dose-dependent manner by pretreatment with WRPE-BF. Moreover, higher dose of WRPE-BF not only decreased infarction area but also effectively redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…A natural product such as WERH that targets PDGF responses in VSMCs is a potential therapeutic strategy in the prevention or inhibition of vascular diseases. The extract of Rosa hybrida is known to be used in the cosmetics industry (20), and it is also known to exert various pharmacological effects, including antioxidant, anti-inflammatory, antimicrobial and neuroprotective effects (20)(21)(22). However, the effect of Rosa hybrida extract on cardiovascular diseases has not yet been examined to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A natural product such as WERH that targets PDGF responses in VSMCs is a potential therapeutic strategy in the prevention or inhibition of vascular diseases. The extract of Rosa hybrida is known to be used in the cosmetics industry (20), and it is also known to exert various pharmacological effects, including antioxidant, anti-inflammatory, antimicrobial and neuroprotective effects (20)(21)(22). However, the effect of Rosa hybrida extract on cardiovascular diseases has not yet been examined to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, researchers have identified gallic acid and volatiles (1-butanol, dodecyl acrylate and cyclododecane) as the main components of R. hybrida (21). Previous studies have established various pharmacological effects for the extract of R. hybrida: it has been noted for its antioxidant, antimicrobial, anti-inflammatory and neuroprotective effects (20)(21)(22). However, the inhibitory effect of water extract of Rosa hybrida (WERH) on vascular diseases has not previously been studied to the best of our knowledge.…”
Section: Rosa Hybrida Extract Suppresses Vascular Smooth Muscle Cell mentioning
confidence: 98%
See 1 more Smart Citation
“…Several studies have reported that inhibiting inflammatory processes that produce cyclooxygenase (COX) -2 (COX-2) and inducible nitric oxide synthase (iNOS) reduce the number of strokes in animal models [2]. Many pro-inflammation enzymes such as iNOS, COXs and xanthine oxidase, participate in oxidative injury during cerebral ischemia [3].…”
Section: Introductionmentioning
confidence: 99%
“…We have reported that extracts of flowers from Rosa hybrida and Rosa rugosa exerted antiallergic effects in vitro cell culture system as well as in vivo systemic and local hypersensitivity models including atopic dermatitis [ 10 11 12 ]. Especially, n-hexane and butanol fractions of white rose petal extract (WRPE) were found to have strong antioxidative activity [ 13 14 ] so that substantially prevented brain infarction in an ischemia-reperfusion model of stroke [ 15 ].…”
mentioning
confidence: 99%